The Effect of Current Ratio (CR), Price to Book Value (PBV), and Return on Assets (ROA) on Stock Price at Surya Citra Media Period 2010-2019 - Noryani; Ahmad Akbar; Endang Nurita (Kusuma Negara Business School, 2021)
The background of this research is the development of the world economy, so Indonesia is one of the developing countries that is a target for domestic and foreign entrepreneurs to increase wealth by buying shares in the form of investment in the capital market. the profit or profit that a company gets becomes a benchmark for a company to reach investors who are hunting for the profits that can be obtained, and investors also consider the stock price that will be issued with the results that investors get, The objectives of this research are: the first is To find out whether CR has a significant effect on the stock price of PT. Surya Citra Media, Tbk., the second is to find out whether PBV has a significant effect on the stock price of PT. Surya Citra Media, Tbk., The Third is To find out whether ROA has a significant effect on the stock price of PT. Surya Citra Media, Tbk and the Fourth is to find out whether PBV and ROA simultaneously have a significant effect on the stock price of PT. Surya Citra Media, Tbk. Stages of this research method is to use secondary data from the financial report data of PT. Surya Citra Media, Tbk listed on the website www.idx.co.id with quantitative descriptive methods using several tests, namely Descriptive Statistics Test, Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test), Multiple Regression Analysis Test, Coefficient of Determination Test, and Hypothesis Testing (T-test and F-test).The results of this study are Current Ratio (CR) partially does not have a significant positive effect on stock prices ,variable Price to Book Value (PBV) partially does not have a significant positive effect on stock prices, the Return On Assets (ROA) variable partially does not have a significant negative effect on stock prices and Variables Current Ratio (CR) Price to Book Value (PBV) and Return On Assets (ROA) simultaneously or simultaneously have no significant effect on the dependent variable, namely stock prices.